The Application of Social Media for Business Communication in The Cassavaâ€™s Production Center â€œKampoeng Teloâ€ in Sub-district of Kandri - nugraha, hari susanta; Farida, Naili; Widayanto, Widayanto; listyorini, sari (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Pengabdian Masyarakat UNDIP 2020, 2020)
Not all craftmen in Cassavaâ€™s Village using social media as a tool for communication in business. The capability for using social media is very low. Its because of their orientation of business still using traditional approach in selling product. On the other hand, in the era of the Covid-19, many craftmen are required to be able to use social media to manage the market. Therefore, there needs to be prepared by introducing to and applying of social media. This process is manifested in social media skills training. Substantially, the skill of using social media in business communication are deciding witch images and messages to be communicated in social media networks. The craftmen attempt to trained using online media and training modules. By improving business communication skills, the craftmen in the Cassavaâ€™s Village can improve market performance.